The hunt for the golden book - Stilton, Geronimo (New York : Scholastic, 2014)
Geronimo Stilton's laptop is stolen just as he is finishing up writing a special book, and he and his friends need to find it in time for the tenth anniversary party. In the bonus mini mystery, Geronimo is sent to the lake to get a news story and photographs of the lake monster for The Rodent's Gazette.
Keywords: Children's stories; Action and adventure fiction